Pediatric swallow assessment instruments: a report by speech and languages pathologist in Colombia and Chile - Grajales Rodríguez, Angie; Moreno P., Lisbey; González G., Sara (Revista de Investigación en Logopedia, 2022)
The prevalence of pediatric users with swallowing / feeding disorders has increased significantly, so carrying out a systematic evaluation process for outpatient and / or hospitalized users, with the use of standardized instruments, can avoid associated complications. The objective of this research was to identify which tests are known and used by Speech-Language Therapist in two Spanish-speaking countries: Colombia and Chile, for the assessment of swallowing in the pediatric population. This is a cross-sectional observational study, in which 36 Speech-Language Pathologists from both countries participated, who answered a survey of 23 items, previously validated by expert judgment. 55.6% (n= 20) indicated that they knew screening tests, 63.89% (n = 23) knew clinical evaluation tests (non-instrumental or subjective), 100% knew instrumental tests (objective) and only 11% (n = 4) knew quality of life tests. Difficulty in the classification of the tests and a greater use of non-standardized tests was generally evidenced, which allows their identification, selection and analytical understanding.
Keywords: Feeding Disorders; Speech-Language Pathology; child